2011
DOI: 10.2754/avb201180030309
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite toxicity assessment in Danio rerio and Poecilia reticulata

Abstract: Nitrite is a natural component of the nitrogen cycle in the environment. Although it usually occurs in low concentrations, elevated concentrations caused by effluents or affected nitrification process can lead to serious health deterioration of fish. Two aquarium fish zebrafish (Danio rerio) and guppy (Poecilia reticulata) are recommended to use as model organisms in toxicity tests. However, their sensitivity to nitrite can differ. The aim of this study was to define acute toxicity of nitrite by the semistatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…The different result that had been reported caused by different fish species, feeding management, design construction, retention times, and plant species affect the different removal efficient [4]. The optimum range such as temperature (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) o C), pH (5.5-7.5), ammonia (<30). Nitrite (<1), nitrate (-), and dissolved oxygen (>3) for plant growth have been reported [27].…”
Section: Fig 1 Layout Of Design Construction Of Aquaponics On Red Tmentioning
confidence: 99%
“…The different result that had been reported caused by different fish species, feeding management, design construction, retention times, and plant species affect the different removal efficient [4]. The optimum range such as temperature (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) o C), pH (5.5-7.5), ammonia (<30). Nitrite (<1), nitrate (-), and dissolved oxygen (>3) for plant growth have been reported [27].…”
Section: Fig 1 Layout Of Design Construction Of Aquaponics On Red Tmentioning
confidence: 99%
“…Costa et al [38] reported that the 96-h LC 50 values for exposure of juvenile pompano (T. marginatus) (0.86 ± 0.21 g) to NO − 2 -N were 39.94, 116.68, and 37.55 mg L −1 at salinity levels of 5, 10, and 30, respectively. Doleželová et al [25] determined that the 96-h LC 50 value for NO , respectively. However, some authors have reported that smaller fish are more sensitive to nitrite than bigger ones.…”
Section: Nitrite Toxicity To Pacific Cod Larvaementioning
confidence: 99%
“…The toxicity of nitrite in fish is primarily a result of its ability to oxidize hemoglobin to methemoglobin, which impairs the oxygen-carrying capacity of blood. [25] The toxicity of nitrite depends on internal and external factors such as water quality, fish species, size, and individual sensitivity. [26,27] Although the acute toxicity of ammonia and nitrite to fish has been reported in many studies, there is no information regarding the acute toxicity of ammonia or nitrite to Pacific cod larvae during the early stages of life.…”
Section: Introductionmentioning
confidence: 99%
“…Both acute and chronic exposures of nitrate and nitrite increase mortality and impair growth and reproduction [4,5]. Some studies in zebrafish at different life stages also reported toxic effects such as developmental defects, high mortality, and growth suppression [6,7]. Though some studies have shown the maternal exposure to high nitrate concentrations in drinking water and food may increase the risk of neuronal defects in infant [8], the information of specific mechanisms in the nervous system affected by nitrate and nitrite exposure is still limited.…”
Section: Introductionmentioning
confidence: 99%